Molecular spectrum of excision repair cross-complementation group 8 gene defects in Chinese patients with Cockayne syndrome type A - Xiaozhu Wang; Yu Huang; Ming Yan; Jiuwei Li; Changhong Ding; Hong Jin; Fang Fang; Yanling Yang; Baiyan Wu; Dafang Chen (Scientific Reports, 2017)
Abstract There are two genetics complementary groups Cockayne syndrome type A and B (CS-A and CS-B OMIM 216400, 133540), which is a rare autosomal recessive segmental progeroid syndrome. Homozygous or compound heterozygous mutations in the excision repair cross-complementation group 8 gene (ERCC8) result in CS-A, and mutations in ERCC6 result in CS-B. Homozygous ERCC6/ERCC8 mutations also result in UV-sensitive syndrome. In this study, twenty-one Han Chinese patients with CS were investigated to identify mutations in ERCC8/ERCC6, of which thirteen cases with CS-A were identified with the mutations of ERCC8. There are five types mutations of ERCC8 in our study, such as exon 4 rearrangement, c.394_398delTTACA, c.299insA, c.843 + 2 T > C, and c.2 T > A. An estimated frequency of exon 4 rearrangement accounts for 69.23% and c.394_398delTTACA accounts for 11.53% in our cohort. Haplotype analysis revealed that the exon 4 rearrangement and c.394_398delTTACA mutations originated from a common founder in the Chinese population respectively. With the identification of three novel ERCC8 mutations, this study expanded the molecular spectrum of known ERCC8 defects, and furthermore, suggests that the exon 4 rearrangement and c.394_398delTTACA mutations may be a common underlying cause of CS-A in the Chinese population, which is different from that in other populations.